Pinning Down Identity in Social Media: Food Cultural Transfer on Pinterest - Lindholm, Leigh Ann (My University, 2016)
This research has been conducted within the realm of where today’s digital media society and the timeless concept of cultural identity overlap. The aim of this thesis is to explore the nature of online cultural identity management. By focusing on the social media platform, Pinterest, this study considers the food-pinning behavior of a group of Americans living in Finland and connects their online actions with their cultural identity. Through an examination of Pinterest as a social space, and even a third place, the relative theoretical literature provides and interesting background for a contemporary discussion on the matter. Literature on food as a cultural marker is also brought into consideration. Using the methods of introspection and an adapted version of virtual ethnography, a study was conducted, and ultimately, the analysis of data obtained from the Pinterest boards of ten individuals shows that the vast majority of food-related information in this setting is US-sourced. A questionnaire provides further insight into the individuals’ Pinterest usage. I argue that pinning is an act of online identity management, whether it is a conscious act or a situational effect, and that using Pinterest maintains and even strengthens these individuals’ cultural identity as Americans. This study adds to current discussions pertaining to transnationalism, globalization, and online cultural identity, as well as opens channels for further research on this dynamic topic, which is needed to understand ourselves as cultural beings in the digital age.